2013
DOI: 10.1021/jp312473b
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Very Short Hydrogen Bond in the Crystal of Nitromalonamide via Car–Parrinello and Path Integral Molecular Dynamics

Abstract: In this paper are presented the results of theoretical studies of the structure in proton motion in a very short O···O and two weak N-H···O intramolecular hydrogen bonds in the nitromalonamide crystal. The dynamics of proton motion in hydrogen bonds were investigated in the NVT ensemble at 298 K using the Car-Parrinello and the path integral molecular dynamics. A very large delocalization of proton in the slightly asymmetrical single well of free energy potential of O-H···O intramolecular hydrogen bond was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 78 publications
(160 reference statements)
0
19
0
Order By: Relevance
“…In an analysis of the importance of vibrationally enhanced catalysis, Kamerlin, Mavri, and Warshel [ 66 ] concluded that dynamical effects and tunneling are irrelevant for enzyme catalysis. Car-Parrinello molecular dynamics calculations were also applied by Durlak et al [ 67 , 68 , 69 ] in investigations of the vibrational structure of compounds like nitromalonamide enol ( 4 ) and 2-acetyl-1,8-dihydroxy-3,6-dimethylnaphthalene ( 7 ), and by Panek et al [ 70 ] in a study of intramolecular hydrogen bonds in a series of 8-hydroxyquinoline N -oxide ( 8 ) derivatives.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of the importance of vibrationally enhanced catalysis, Kamerlin, Mavri, and Warshel [ 66 ] concluded that dynamical effects and tunneling are irrelevant for enzyme catalysis. Car-Parrinello molecular dynamics calculations were also applied by Durlak et al [ 67 , 68 , 69 ] in investigations of the vibrational structure of compounds like nitromalonamide enol ( 4 ) and 2-acetyl-1,8-dihydroxy-3,6-dimethylnaphthalene ( 7 ), and by Panek et al [ 70 ] in a study of intramolecular hydrogen bonds in a series of 8-hydroxyquinoline N -oxide ( 8 ) derivatives.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…For example, Buemi and Zuccarello [ 81 ] computed an anharmonic PT2 wavenumber ν OH = 1428 cm −1 for the very short intramolecular hydrogen bond in nitromalonamide enol ( 4 ), but the P(Harm) value is 1920 cm −1 [ 18 ]. The P(harm) prediction was subsequently supported by the results of sophisticated molecular dynamics calculations [ 67 ]. In fact, the PT2 procedure appears to overestimate the wavenumber shifts due to strong intramolecular hydrogen bonding, leading to the prediction of too low OH stretching wavenumbers [ 18 ].…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…The labelling of fluorine atoms (a and b) was done arbitrarily and kept consistent during the analysis deviation for FÁ Á ÁD distance in PIMD is 0.097 Å and in our Born-Oppenheimer MD simulation it equals to 0.063 Å. In general, nuclear quantum effects are without a question important for a neat description of strong H-bond parameter distribution, [21][22][23][24] however in this paper we focus on solvent-solute interactions and comparisons of different types of specific interactions in condensed phase. Note, that the distribution of spectroscopic parameters is rather broad even without the influence of fluctuating solvent molecules in the solvation shell.…”
Section: Fhf à In Vacuummentioning
confidence: 99%
“…39 For various polymorphic glycine forms, the plane wave pseudopotential methodology has been already successfully applied to produce static chemical shifts, although the static values sometimes significantly deviate from experiment. 40 In the other studied system, solid 2-nitromalonamide (NMA, Figure 1 43 The molecule is also interesting for a large anomalous temperature dependence of 2 H quadrupolar coupling in deuterated NMA. Normally, the magnitude of quadrupolar couplings is reduced with increasing temperature, due to vibrational and librational motions.…”
Section: Introductionmentioning
confidence: 97%